Pengambilan Resiko dan Intensi Berwirausaha Pada Mahasiswa - Yudhaningrum, Lupi; Akbar, Zarina; Erik, Erik; Fadhalah, R.A.; Ismi, Wa Ode Imani (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
This study aims to identify whether there is a significant relationship between risk-taking and student entrepreneurship intentions. In this study using quantitative methods with a psychological measurement scale. The technique in this research uses incidental sample technique with 260 respondents. Measuring instruments used in this study are the Entrepreneurial Intention Questionnaire (EIQ) and DOSPERT (Domain-Specific Risk-Taking). The statistical analysis used in this study is Kendall's tau-b test. The results showed Sig. (2-tailed) <0.05 which means that there is a significant relationship between risk-taking and entrepreneurial intentions in students. The relationship in this study is positive in that the higher the risk-taking of students, the entrepreneurial intentions are also high. Keywords: Risk-Taking, the Entrepreneurial Intentions, Students